THE EMERGENCE AND DEVELOPMENT OF THE MANAGEMENT SYSTEM FOR THE PROTECTION OF CULTURAL HERITAGE OBJECTS IN UZBEKISTAN - Rejabov Giyosiddin Qutbidinovich (Journals Park Publishing, 2022)
This article describes in detail the stages of the creation and development of the system of protection and management of cultural heritage objects in Uzbekistan. In particular, the system of protection of cultural heritage objects of the period before and after the independence of our country has been deeply analyzed. Also, scientific proposals on the improvement of the system of protection of cultural heritage objects and its further development have been developed.
Keywords: cultural heritage, cultural monument, archeology